Empowerment of Farmer's Salt Smallholder and their Welfare - Purwiyono, Bambang; Prihatminingtyas, Budi; Pudjiastuti, Agnes Quartina (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 2 (2022): Vol 16 No 2 (2022), 2022)
Efforts to fulfill salt self-sufficiency target and improve quality of smallholder's salt must be able to increase  farmers’ income. Many policies have been implemented to achieve it, including empowering them through table salt technology. The study aims to analyze: 1) implementation of PUGAR, 2) impact of PUGAR on the farmers’ welfare, and 3) factors that influence farmers’ production in Pasuruan Regency. Primary data were collected from 40 farmers who were selected by simple random sampling. Data were analyzed using simple and multiple linear regression. The results showed that implementation of PUGAR was accepted by all salt processing communities and well implemented. There are four things that are very important for farmers:  extension policy of PUGAR, the program is carried out on target, appropriate to regulations, and compatible to existing resources. PUGAR was perceived by farmers as being able to improve their welfare. The better farmers' perception, the more prosperous they will be. Factor that had a significant effect on salt production is only number of table salts. Age, education, number of family members, experience, amount of fuel, number of workers, length of salt production process, and price of salt had no effect on salt production. Limitation of the study is that welfare of salt farmers was just not measured, because it uses their perceptions with a Likert scale. Other researchers can measure welfare of farmers using equivalent variation (EV) and complementary variation (CV) in order to know quantitative changes in welfare.